Zakat dalam Perspektif Hukum Positif: Antara Kewajiban Agama dan Ketaatan Hukum Negara - Kamalin, Muhammad; Zakir, Muhammad (EL-EMIR Institute, 2025)
This study discusses the position of zakat within the perspective of positive law in Indonesia, focusing on the relationship between religious obligations and compliance with state law. Zakat, as a religious obligation in Islam, is normatively regulated in the Zakat Management Law; however, its implementation is not yet fully legally binding. The research employs a normative legal method with statutory and conceptual approaches. The results show that zakat is still positioned as a moral and religious obligation rather than a legal obligation enforced by state sanctions. Nevertheless, there are opportunities to strengthen regulations and integrate zakat into the national legal system to enhance its role in social and economic development.